2021
DOI: 10.1002/adem.202100322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Nanotube Infiltration on a Shape Memory Polymer‐Based Device for Brain Aneurysm Therapeutics: Design and Characterization of a Joule‐Heating Triggering Mechanism

Abstract: Current endovascular therapies for intracranial aneurysms face limitations that include aneurysm recurrence and incomplete occlusion. These challenges can potentially be addressed by occluding the aneurysm space with shape memory polymers (SMPs) that are tailorable to patient‐specific aneurysm geometries to improve the suboptimal treatment outcomes associated with coil embolization. However, deployment of the SMP‐based device into the aneurysm requires external stimuli to trigger shape recovery. Thus, herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…SMP/CNT foams emit heat when the direct current is applied, allowing the recovery of the compressed foam (Figure 6). However, we also observed that CNT infiltration reduced T g of the material and deteriorated its capacity to withstand cyclic deformation [58]. Other researchers have also found similar behaviors for CNT-infiltrated SMP composites [85,86].…”
Section: Joule Heating Activationsupporting
confidence: 83%
See 3 more Smart Citations
“…SMP/CNT foams emit heat when the direct current is applied, allowing the recovery of the compressed foam (Figure 6). However, we also observed that CNT infiltration reduced T g of the material and deteriorated its capacity to withstand cyclic deformation [58]. Other researchers have also found similar behaviors for CNT-infiltrated SMP composites [85,86].…”
Section: Joule Heating Activationsupporting
confidence: 83%
“…Currently, SMP-based endovascular devices are under development so that they can be utilized in a similar manner. SMP design for endovascular devices can follow two major approaches: (i) SMP-coated coils such as Trellix [19,46]; and (ii) coil-free SMPs foams [55][56][57][58]. SMP-coated coils have a similar goal to the hydrogel coils: increasing the packing density may augment the volume of the coil.…”
Section: Porous Shape Memory Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…[35] Our findings in this modified protocol will be applied to the development of a novel coil-free endovascular device. We have developed a shape memory polymer (SMP) for endovascular embolization of patient-specific aneurysm geometries, [36][37][38][39] and we believe that this elastase-induced aneurysm formation protocol can aid in the translation of our material to the pre-clinical setting. We plan to test our material with a statistically powerful sample size, to determine the pre-clinical safety and effectiveness of our SMP device (measured using RROC scale, Fig.…”
Section: Applications For Endovascular Device Testingmentioning
confidence: 99%